2019
DOI: 10.1038/s41598-019-42763-0
|View full text |Cite
|
Sign up to set email alerts
|

K1 gene transformation activities in AIDS-related and classic type Kaposi’s sarcoma: Correlation with clinical presentation

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) causes both AIDS-related Kaposi’s sarcoma (KS) and classic KS, but their clinical presentations are different, and respective mechanisms remain to be elucidated. The KSHV K1 gene is reportedly involved in tumorigenesis through the immunoreceptor tyrosine-based activation motif (ITAM). Since we found the sequence variations in the K1 gene of KSHV isolated from AIDS-related KS and classic KS, we hypothesized that the transformation activity of the K1 gene contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The procedure for retrovirus production and the construction of viral protein expressing MEFs have been described previously [ 16 ]. Briefly, the plasmids pMSCV- puro - 6E6 , pMSCV- puro - 11E6 , pMSCV- puro - 11E7 and pMSCV- neo - LMP-1 were transfected into packaging cell lines PT-67 (Clontech) using Lipofectamine 2000 (Thermo Fisher Scientific) and incubated for 48 h. Retroviruses harboring the various HPV and/or EBV genes were generated, and CF-1 cells were then infected with the viruses.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for retrovirus production and the construction of viral protein expressing MEFs have been described previously [ 16 ]. Briefly, the plasmids pMSCV- puro - 6E6 , pMSCV- puro - 11E6 , pMSCV- puro - 11E7 and pMSCV- neo - LMP-1 were transfected into packaging cell lines PT-67 (Clontech) using Lipofectamine 2000 (Thermo Fisher Scientific) and incubated for 48 h. Retroviruses harboring the various HPV and/or EBV genes were generated, and CF-1 cells were then infected with the viruses.…”
Section: Methodsmentioning
confidence: 99%
“…ORF K1 measures approximately 1080 bp [46] (Table 1). The K1 transmembrane protein is an oncoprotein [64] encoded by this gene, described in 1998 by Lee et al [65]. K1 is 279 amino acids in length [46] and is primarily expressed during KSHV lytic replication [66].…”
Section: Orf K1 (K1)mentioning
confidence: 99%
“…In addition, K1 transgenic mice develop spindle cell sarcomatoid tumors and plasmablastic lymphoma, thought to be mediated by the activation of NF-κB and the B-cell transcription factor, Oct2 [70,71]. K1 is thought to be involved in the activation of tyrosine immunoreceptors that also activate a cascade linked to the tumorigenesis of KS [64].…”
Section: Orf K1 (K1)mentioning
confidence: 99%
“…On the other hand, a study has shown in vitro that the K1 gene in the epidemic form was associated with a higher transforming activity compared with those in the classic form. This higher activity was also correlated with the severity of the clinical presentation [ 136 ].…”
Section: Epidemiologymentioning
confidence: 99%